The Biogeographies of the Blue Bird-of-Paradise: From Sexual Selection to Sex and the City. Issue 4 (21st May 2019) - Patchett, Merle
Abstract: This article takes as its starting point an encounter with a preserved blue bird-of-paradise skin. Though rare, the bird became wildly famous after it perched atop the head of Carrie Bradshaw during Sex and the City: The Movie . However, where in the movie the bird-skin acted as Carrie's something blue, I mobilize it in this article as a "telling example" of near-extinction. This is because the blue bird-of-paradise is but one of the millions of Paradisaea that were hunted, traded, shipped, and lusted after since their earliest forms of commodification. And as the theory of sexual selection confirms, biographical entitlement cannot be assigned to a singular agent in the blue bird-of-paradise's story, which is why this article will chart its biogeographies: from New Guinea rainforests to New York streets. Here, instead of tracing the blue bird-of-paradise's individual commodity biography, it becomes an act of tracing and placing the bird-skin within the life and death worlds of human-animal relations that produced, mobilized, and maintain(ed) it as a commodity over time and space. In doing so, the article makes two important contributions to the field of social history. First, by conceptually focusing on the relations that produce lives, things, and worlds, it challenges the certainty that anchors the narration of biographies to the singular and anthropocentric embodiment of "a life." Second, mapping the biogeographies of a "lively" commodity, such as a preserved bird-of-paradise, offers the opportunity of highlighting the significant role so-called natural species and histories can play in shaping human histories.